Deciphering complexity: TULP1 variants linked to an atypical retinal dystrophy phenotype - Esteve-Garcia, Anna; Cobos, Estefania; Sau, Cristina; Padró-Miquel, Ariadna; Català-Mora, Jaume; Barberán-Martínez, Pilar; Millán, José M.; García-García, Gema; Aguilera, Cinthia (Frontiers in Genetics, 2024)
Introduction – TULP1 exemplifies the remarkable clinical and genetic heterogeneity observed in inherited retinal dystrophies. Our research describes the clinical and molecular characteristics of a patient manifesting an atypical retinal dystrophy pattern, marked by the identification of both a previously unreported and a rarely encountered TULP1 variants. Methods – Whole exome sequencing was performed to identify potential causative variants. The pathogenicity of the identified TULP1 variants was evaluated through in silico predictors and a minigene splice assay, specifically designed to assess the effect of an unreported TULP1 variant. Results – We identified two TULP1 gene variants in a patient exhibiting unusual and symmetrical alterations in both retinas, characterized by an increase of autofluorescence along the distribution of retinal vessels. These variants included a known rare missense variant, c.1376T>C, and a novel splice site variant, c.822G>T. Segregation analysis confirmed that these variants were in trans. Discussion – Our data supports that individuals with biallelic TULP1 variants may present with a unique pattern of macular degeneration and periarteriolar vascular pigmentation. This study highlights the importance of further clinical and molecular characterization of TULP1 variants to elucidate genotype-phenotype correlations in the context of inherited retinal dystrophies.